2022
DOI: 10.1111/gwao.12920
|View full text |Cite
|
Sign up to set email alerts
|

“That's bang out of order, mate!”: Gendered and racialized micro‐practices of disadvantage and privilege in UK business schools

Abstract: The existence of gendered and racialized inequalities in academia has been well documented. To date, research has primarily addressed the intersectional disadvantages faced by members of minority groups with much less attention paid to the privileges experienced by dominant group members.This paper draws on 21 interviews and 36 audio-diary entries completed by a diverse group of senior higher education leaders who have successfully navigated the career ladder in UK business schools. By juxtaposing minority wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…However, a recent Harvard Business Review Analytic Services research report (2021) on EDI revealed that whilst many organisations are trying to advance their EDI agendas, few have managed to make satisfactory inroads. Organisations struggle to leverage the strategic potential of EDI (Ely & Thomas, 2020; Newburry et al., 2022), which can only be achieved if EDI is holistically and deeply embedded into organisational cultures (Cassell et al., 2022; Śliwa et al., 2022) and aligned with shared values (Umeh et al., 2022) rather than solely linked to non‐discriminatory policies. EDI‐related initiatives and diversity management are particularly challenging to implement in multinational companies (MNCs), not least because of problems with legitimacy, in particular among non‐HR managers (Davis et al., 2016; Kirton & Greene, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent Harvard Business Review Analytic Services research report (2021) on EDI revealed that whilst many organisations are trying to advance their EDI agendas, few have managed to make satisfactory inroads. Organisations struggle to leverage the strategic potential of EDI (Ely & Thomas, 2020; Newburry et al., 2022), which can only be achieved if EDI is holistically and deeply embedded into organisational cultures (Cassell et al., 2022; Śliwa et al., 2022) and aligned with shared values (Umeh et al., 2022) rather than solely linked to non‐discriminatory policies. EDI‐related initiatives and diversity management are particularly challenging to implement in multinational companies (MNCs), not least because of problems with legitimacy, in particular among non‐HR managers (Davis et al., 2016; Kirton & Greene, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The "leaky pipeline" is a persistent phenomena as read in our first paper by Martyna Śliwa, Lisi Gordon, Katy Mason and Nic Beech (2022) "'That's bang out of order, mate! ': Gendered and racialized micro-practices of disadvantage and privilege in UK business schools" funded by the British Academy of Management.…”
mentioning
confidence: 99%